2022
DOI: 10.1093/mnras/stac368
|View full text |Cite
|
Sign up to set email alerts
|

Explaining deep learning of galaxy morphology with saliency mapping

Abstract: We successfully demonstrate the use of explainable artificial intelligence (XAI) techniques on astronomical datasets in the context of measuring galactic bar lengths. The method consists of training convolutional neural networks on human classified data from Galaxy Zoo in order to predict general galaxy morphologies, and then using SmoothGrad (a saliency mapping technique) to extract the bar for measurement by a bespoke algorithm. We contrast this to another method of using a convolutional neural network to di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…3). The principal difference between our approach and the existing ones (see, for example, recent works [56,[84][85][86]) is the usage of 1) the pre-defined training-test split through adversarial validation of the classification accuracy on the inference-like test set, and 2) the specific data augmentation, which allowed us to decrease the difference in galaxy images related to the stellar magnitudes between the GZ2 and inference data sets.…”
Section: Cnn Five-class Morphological Classifiermentioning
confidence: 99%
See 1 more Smart Citation
“…3). The principal difference between our approach and the existing ones (see, for example, recent works [56,[84][85][86]) is the usage of 1) the pre-defined training-test split through adversarial validation of the classification accuracy on the inference-like test set, and 2) the specific data augmentation, which allowed us to decrease the difference in galaxy images related to the stellar magnitudes between the GZ2 and inference data sets.…”
Section: Cnn Five-class Morphological Classifiermentioning
confidence: 99%
“…13. Bhambra et al [85] proposed the explainable artificial intelligence (XAI) techniques to measure galactic bar lengths and bulge-to-disk ratio. They used the Hoyle bar length catalog [132] vs. GZ annotated data and demonstrated that XAI works more successfully in predictions of a bar feature.…”
Section: Notes On Problem Points Of Cnn Image-based Galaxy Classifica...mentioning
confidence: 99%
“…It compares the average relevance maps and the topo-plots for binary masks for various methods, including LRP-based methods. [17] uses saliency mapping by adding Gaussian noise to the input images. Its data set contains many kinds of galaxy images, and it uses some data augmentation techniques such as random rotations and flips.…”
Section: Introductionmentioning
confidence: 99%
“…We call each divided sub-image a part, and then we make each modified image by LIME based methods [7,13] feature (or feature masks) [10,11,15,22,25] LRP-based methods [14,16,21] others [9, 12, 17-20, 23, 24] Table 1 compares each paper from the related works by the category of the method used. Among [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], [6,8] use the difference of the input values of a neural network to generate explanations. We can compare them with our method.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al (2022) introduced a continuous depth version of the Residual Network called Neural Ordinary Differential Equations (NODE) which obtained an accuracy between 91%-95% depending on the classifications. DL methods used for galaxy morphological classifications are discussed in Tuccillo et al (2016), Khan et al (2019), Ghosh et al (2020), Bhambra et al (2022), Zhang et al (2022) and Vavilova et al (2022).…”
mentioning
confidence: 99%